Generalized orthogonal transmission system and its efficient implementation method - ZHANG Deng-yin; ZHENG Bao-yu (Tongxin xuebao)
Based on subband transformation theory, a general model for orthogonal transmultiplexers is constructed. Besides several popular multiuser communication applications such as TDMA, FDMA and CDMA, it can also describe multi-carrier systems such as OFDM and multi-carrier CDMA system, the combination of MC modulation and CDMA. The model, whose structure is equivalent to DFT filterbanks, can be efficiently realized with the help of FFT and polyphase filterbanks. MC system realized in this paper allows the variation of the subcarrier spacing with a fine granularity and its complexity is comparable to the one of OFDM with windowing. The simulation results of MCSIS （a kind of MC system with soft impulse shaping ） show that its performance is better than the one of OFDM on the same condition. MC-CDMA performs better than OFDM thanks to its built-in robustness against frequency-selective fading.